Interfaith Dialogue and the Science-and-Religion Discussion - Moore, James F. (Zygon, 2002)
The science-and-religion dialogue has so often assumed that the key issues for discussion are those that have arisen within the Western Christian religious and intellectual tradition that little interest has been devoted to the possible insights that the presence of non-Christian voices in the dialogue might bring. In the following I explore the benefits of a truly multireligious dialogue on science and religion and offer a model for integrating various religious perspectives into the science-and-religion dialogue. Of course, taking the multifaith perspectives of the religions seriously also means making a dialogue between religions a component of the science-and-religion dialogue, and I discuss how such a dialogue might unfold along with key ideas that might emerge in ever more interesting ways once the dialogue begins.